The method for distribution of wavelengths in DWDM networks using meta-heuristic BCO-RWA - Агеев, Д.В.; Переверзев, А.А. (Radiotekhnika, 2012)
The analysis of existing methods for solving the problem of the routes choice and route assignments to wavelengths distribution is carried out. The method for solving the problem of the choice of routes and route assignments distribution of wavelengths, which is based on a meta-heuristic algorithm BCO-RWA is developed.